2020
DOI: 10.1111/bcp.14491
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug–drug interaction in an elderly human immunodeficiency virus population: Comparison of 3 expert databases

Abstract: Aims Polypharmacy increase the risk of drug–drug interactions (DDIs) in the elderly population living with human immunodeficiency virus (HIV). Several expert databases can be used to evaluate DDIs. The aim of the study was to describe actual DDIs between antiretroviral drugs and comedications in an elderly population and to compare grading of the DDIs in 3 databases. Methods All treatments of HIV‐infected subjects aged 65 years and older were collected in 6 French HIV centres. Summary of Product Characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Risk of bias analysis highlighted a few key areas of risk. Five studies [12][13][14][15][16] only selected patients older than a certain age threshold. These studies may therefore skew toward more clinically significant DDIs due to increased polypharmacy in older age groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk of bias analysis highlighted a few key areas of risk. Five studies [12][13][14][15][16] only selected patients older than a certain age threshold. These studies may therefore skew toward more clinically significant DDIs due to increased polypharmacy in older age groups.…”
Section: Resultsmentioning
confidence: 99%
“…The full risk of bias analysis for included articles are shown in Figure S4, Supplemental Digital Content, http://links.lww.com/QAI/B994 and funding sources in Table S5, http://links.lww.com/QAI/B994. 53 No Brazil Liverpool Ruellan 2020 15 No France Liverpool, French DDI Thesaurus, SmPC ✓ Schlaeppi 2020 54 No Tanzania Liverpool ✓ Funke 2021 55 25. The characteristics of the 34 included studies are available in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Databases for assessing DDIs are available through subscription and open‐access platforms. Previous studies have evaluated ARVs with concomitant medications and demonstrated discrepancies between online DDI databases with older ARVs 6–9 . Since these studies, newer agents have been approved for the treatment of HIV.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Previous studies have evaluated ARVs with concomitant medications and demonstrated discrepancies between online DDI databases with older ARVs. 6 , 7 , 8 , 9 Since these studies, newer agents have been approved for the treatment of HIV. The aim of our study was to compare interaction identification and severity classification for commonly used ARVs and concomitant medications between six different online DDI databases.…”
Section: What Is Known and Objectivementioning
confidence: 99%